2007
DOI: 10.1021/ma071732f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Surface Morphology of Pendant Polyhedral Oligomeric Silsesquioxane Perfluorocyclobutyl Aryl Ether Copolymers

Abstract: The synthesis and characterization of solution processable, semi-fluorinated perfluorocyclobutyl (PFCB) aryl ether polymers possessing covalently bound pendant polyhedral oligomeric silsesquioxanes (POSS) cages is reported. The synthesis of POSS aryl trifluorovinyl ether (TFVE) monomers was accomplished by the condensation of commercial monosilanolalkyl-POSS with a TFVE-functionalized chlorosilane. POSS TFVE monomers were elucidated by 1H, 19F, 13C, and 29Si NMR spectroscopy, ATR-FTIR analysis, and elemental (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…Even for pentablock copolymers with the same structure, the sample S2, which had a higher POSS percentage, showed a significant increase in the  r value in comparison with that of S3. It has been suggested that the increased surface roughness generated by POSS has a more important effect on WCA than surface composition does [38,39]. From Table 4, it could also be seen that the ice shear strength of S3 had the lowest value (247 ± 20 kPa) in all the samples, though they had a similar surface energy ca.…”
Section: Surface Propertiesmentioning
confidence: 92%
“…Even for pentablock copolymers with the same structure, the sample S2, which had a higher POSS percentage, showed a significant increase in the  r value in comparison with that of S3. It has been suggested that the increased surface roughness generated by POSS has a more important effect on WCA than surface composition does [38,39]. From Table 4, it could also be seen that the ice shear strength of S3 had the lowest value (247 ± 20 kPa) in all the samples, though they had a similar surface energy ca.…”
Section: Surface Propertiesmentioning
confidence: 92%
“…POSS are hybrid cage molecules related to silicones, with a chemical structure (RSiO 1.5 ) consisting of an inorganic core (SiO 1.5 ) and organic side groups (R). As a result of this structure, POSS can be incorporated into polymer systems in a number of ways including blending, grafting and copolymerization [3][4][5][6][7][8][9]. Many variations of POSS molecules can be synthesized; a few of greatest interest to the current srudy are illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 Polyhedral oligomeric silsesquioxanes of interest to this study while its variety of organic periphery groups allows for reaction or other interactions with the host polymer. By modifying the type and ratio of the inorganic cage to the surrounding organic groups, the properties of POSS can span the gap from inorganic materials to organic substances The ease with which the organic periphery of POSS molecules can be modified is a major reason for the great interest in these materials as polymer modifiers, since the ability of an additive to be dispersed within a polymer matrix depend on matching structures and thermodynamic interactions [5,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding POSS to polymers can bring about significant improvements in the bulk properties of these polymers such as increased thermal stability, hardness, wear resistance, oxidative resistance, mechanical properties and decreased flammability and viscosity during processing [9][10][11][12][13][14][15][16][17][18][19][20]. There are also some limited studies on the surface hydrophobicity of POSS-based polymer nanocomposites [9,10,14,15,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%